Respiratory Distress in Pediatric Dengue Patients: Coinfections, Diagnosis Challenges and Treatment Strategies in an Endemic Setting (Journal of Brahmanbaria Medical College, 2026)
Background: Respiratory distress complicating pediatric dengue fever cases underscores the significance of timely diagnosis and treatment, especially in endemic settings like Bangladesh. Coinfections with respiratory pathogens add to the complexity of management and treatment. This study aims to shed light on the coinfection and clinical implications of coinfections in pediatric dengue patients.Case Presentation: We present a case report of two children with dengue fever who were diagnosed with coinfections, including Salmonella, Acinetobacter species, and Staphylococcus hominis. These patients exhibited severe clinical manifestations (Persistent fever, respiratory distress), and positive dengue serology results. Diagnostic workup revealed coinfections, highlighting the need to consider alternative pathogens in dengue patients.Conclusion: Coinfections in dengue patients present unique challenges due to overlapping clinical features and the potential for delayed or missed diagnoses. The endemic nature of salmonella and dengue in Bangladesh increases the likelihood of co-occurrence. Understanding these associations is crucial for accurate diagnosis and timely intervention.Journal of Brahmanbaria Med. Coll. Volume 07 Issue 01 Jan 2025 ; 40-45